Reconstruction of the figurative component and structure of the concept of fool according to the Proto-Slavic vocabulary - Masliy, Olena (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2022)
From the point of view of linguistics, reconstruction of the ancient conceptions, depicted in the proto-language, allows us to reveal the evolutionary relationship between language units of a proto-language, certain language family, and certain language. Similar regularities are described by the theory of etymological (or cultural) word memory.The named theory is sufficiently developed and well-known, but until now it has not focused attention on the connection of the first and ancient meanings of the word with conceptual semantics. The author of the article intends to investigate specified relationship and present materials on this issue in a series of publications, the first of which is this article. This determines the novelty of the proposed subject. Its relevance is determined by the original aspect of the description of the concept: the reconstruction of its figurative component and original meanings based on the materials of the Proto-Slavic vocabulary.The purpose of the study is to reconstruct the origins of the modern concept of fool based on the data of the Proto-Slavic vocabulary.For this purpose, the work creates a typology of the meanings of words with the root *-dur-; the structure of the concept of fools is reconstructed and compared based on the material of the Proto-Slavic vocabulary, the vocabulary of the Russian language and dialects; the etymology of the root *-dur- and the "prototypes" associated with its semantics are described; the figurative component of the concept is reproduced.We conclude that the core meanings of the Proto-Slavic and Russian concepts of fools coincide with incompleteness. And "prototypes" that arise as a result of the etymological reconstruction of the root *dur- and the central image of the hypothetical Proto-Slavic concept are correlated, which is evidence of the regularities of meaning formation, described by the theory of the etymological memory of the word, which is revealed in the features of concept formation.